2016
DOI: 10.1002/2016gl069554
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional attenuation model of Sierra Negra Volcano, Galápagos Archipelago

Abstract: The shallow magma system beneath Sierra Negra was imaged using attenuation tomographic methods. The t∗ spectral decay method for P wave phases was used to highlight regions of high Qp−1 which suggest the presence of magma melt. High‐ Qp−1 anomalies ranging from 0.005 to 0.04 are concentrated below the caldera from 0.5 to 10.5 km depths. Attenuation is sensitive to temperature and fluid presence; thus, this high attenuation is interpreted as possible zones of magma accumulation. An imaged shallow body is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
(75 reference statements)
4
9
0
Order By: Relevance
“…Sierra Negra (Rodd et al, 2016). This theory is in broad agreement with studies of other Galapagos volcanoes, such as Bagnardi and Amelung (2012), which identified at least two areas of magma storage below Fernandina Volcano, and Stock et al (2018), which identified two magma reservoirs beneath Wolf Volcano.…”
Section: Application To Sierra Negrasupporting
confidence: 86%
See 2 more Smart Citations
“…Sierra Negra (Rodd et al, 2016). This theory is in broad agreement with studies of other Galapagos volcanoes, such as Bagnardi and Amelung (2012), which identified at least two areas of magma storage below Fernandina Volcano, and Stock et al (2018), which identified two magma reservoirs beneath Wolf Volcano.…”
Section: Application To Sierra Negrasupporting
confidence: 86%
“…Between the 2005 and 2018 eruptions, the deployment of a temporary broadband seismic network termed the SIGNET array (Tepp et al., 2014) has provided additional insights into the structure of the crust beneath Sierra Negra. Body wave tomography has been used to infer the existence of large low velocity zone at depths of 8–15.5 km below sea level (BSL) coupled with smaller areas of high and low velocities at depths of 3–15.5 km BSL (Tepp et al., 2014), while attenuation tomography has been used to infer the existence of separate low velocity zones from 0.5–3 and 3–10.5 km BSL (Rodd et al., 2016). Combining these measurements with the geodetic studies of deformation before the 2005 eruption has led to the conclusion that both a shallow magma chamber and a deeper magma chamber embedded in a larger mush zone exist below Sierra Negra (Rodd et al., 2016).…”
Section: Application To Sierra Negramentioning
confidence: 99%
See 1 more Smart Citation
“…Earthquake magnitudes are estimated using a local magnitude scale and distance correction terms for incipient seafloor spreading zones where local attenuation is high [Keir et al, 2006], in the absence of a local magnitude scaling relation. This scaling is consistent with the high P-wave attenuation at depths of 0.5-8.5 km below sea level estimated by the attenuation tomography model of Rodd et al [2016]. A site-specific magnitude scale awaits a time series that spans an eruption cycle.…”
Section: Magnitudessupporting
confidence: 80%
“…The geometry of the bottom of the sill(s) is poorly constrained by surface deformation patterns [Yun et al, 2007]. The 3D attenuation model of Rodd et al [2016] reveals patchy, highly attenuating zones between 0.5 km -3 km below sea level, interpreted as shallow magma bodies. The zone between the shallow sill and the deeper crystal mush zone remained poorly determined.…”
Section: Introductionmentioning
confidence: 99%